A machine learning approach for the recognition of melanoma skin cancer on macroscopic images - Jairo Hurtado; Francisco Reales (Universitas Ahmad Dahlan, 2021)
In the last years, computer vision systems for the detection of skin cancer have being proposed, specially using machine learning techniques for the classification of the disease and features based on the ABCD dermatology criterion, which gives information on the status of the skin lesion based on static properties such as geometry, color and texture, making it an appropriate criterion for medical diagnosis systems that work through images. This paper proposes a novel skin cancer classification system that works on images taken from a standard camera and studies the impact on the results of the smoothed bootstrapping, which was used to augment the original dataset. Eight classifiers with different topologies (KNN, ANN and SVM) were compared, with and without data augmentation, showing that the classifier with the highest performance as well as the must balanced one was the ANN with data augmentation, achieving an AUC of 87.1%, which saw an improvement from an AUC of 84.3% of the ANN trained with the original dataset.